Taxing the financial sector : concepts, issues, and practices (Washington, D.C : International Monetary Fund, 2004)
Business
2005-04-11
Keywords: Tax; Financial sector; Fiscal policy; Insurance - Taxation; Value added tax; Financial instruments; Financial services; Taxation